Expression of Carnitine Palmitoyltransferase I Isotypes in Gingival Tissues of Human Periodontitis - Yue Shen; Lu Lin; Weijun Yu; Zhurong Cui; Tingting Lin; Shucheng Hu; Yuanjie Shi; Yuting Gu; Min Jin; Eryi Lu (International Dental Journal, 2025)
Introduction and aims: Carnitine palmitoyltransferase I (CPT1), the rate-limiting enzyme of fatty acid oxidation, plays a crucial role in inflammation. However, the relation between CPT1 and periodontitis is obscure. This study aimed to reveal the expression pattern of CPT1 (CPT1A, CPT1B, CPT1C) in periodontitis and their correlation with clinical parameters. Methods: The public dataset was used to identify biological processes related to lipid metabolism and validate the differential expression of CPT1 between healthy and periodontitis groups. Forty-seven healthy gingival samples and 47 periodontitis gingival samples were gathered. Subsequently, real-time quantitative polymerase chain reaction was used to measure CPT1 expression. Their protein levels were assessed using western blotting and histological analysis. Single-cell analysis using GSE164241 was conducted to observe CPT1A and CPT1C expression in different cell types, followed by immunofluorescence validation. Finally, the correlation of CPT1A and CPT1C with clinical parameters was estimated, and receiver operating characteristic curves were constructed. Results: Most biological processes related to lipid metabolism shared the gene CPT1A, and the expression of CPT1A and CPT1C in the periodontitis group was upregulated. Besides, both CPT1A and CPT1C were expressed mainly in endothelial cells, and their expression was elevated in endothelial cells of periodontitis. Furthermore, CPT1A and CPT1C were correlated with clinical parameters, and CPT1A could serve as a diagnostic marker of periodontitis. Conclusions: Our findings elucidated the expression of CPT1 in gingival tissues of periodontitis and demonstrated the association of CPT1 with periodontitis. Clinical relevance: This study found the positive correlation of the expression of CPT1A and CPT1C in gingival tissues with clinical parameters, which might lay a foundational framework for further elucidating the underlying mechanisms of lipid metabolism and periodontitis and pave the way for exploring potential therapeutic targets.